A systems genetics analysis in Eucalyptus reveals coordination of metabolic pathways associated with xylan modification in wood‐forming tissues. Issue 4 (20th July 2019) - Wierzbicki, Martin P.; Christie, Nanette; Pinard, Desré; Mansfield, Shawn D.; Mizrachi, Eshchar; Myburg, Alexander A.
Summary: Acetyl‐ and methylglucuronic acid decorations of xylan, the dominant hemicellulose in secondary cell walls (SCWs) of woody dicots, affect its interaction with cellulose and lignin to determine SCW structure and extractability. Genes and pathways involved in these modifications may be targets for genetic engineering; however, little is known about the regulation of xylan modifications in woody plants. To address this, we assessed genetic and gene expression variation associated with xylan modification in developing xylem of Eucalyptus grandis × Eucalyptus urophylla interspecific hybrids. Expression quantitative trait locus (eQTL) mapping identified potential regulatory polymorphisms affecting gene expression modules associated with xylan modification. We identified 14 putative xylan modification genes that are members of five expression modules sharing seven trans ‐eQTL hotspots. The xylan modification genes are prevalent in two expression modules. The first comprises nucleotide sugar interconversion pathways supplying the essential precursors for cellulose and xylan biosynthesis. The second contains genes responsible for phenylalanine biosynthesis and S ‐adenosylmethionine biosynthesis required for glucuronic acid and monolignol methylation. Co‐expression and co‐regulation analyses also identified four metabolic sources of acetyl coenxyme A that appear to be transcriptionally coordinated with xylan modification. Our systems genetics analysis may provide new avenues for metabolic engineering to alter wood SCW biology for enhanced biomass processability.